Acid reduction and Helicobacter pylori treatment in pyloric stenosis: A prospective study - Sadık YILDIRIM; Levent ERDEM; Hakan M. KÖKSAL; Adil BAYKAN; Halil İ. MEDE and Ömer KURT (Turkish Journal of Gastroenterology, 2019)
-